ANALYSIS OF THE EFFECT OF MACROPRUDENTIAL POLICY INSTRUMENTS ON COMMERCIAL BANK LIQUIDITY IN INDONESIA - Maulidina Nur Budiastuti; Harya Kuncara Wiralaga; Siti Fatimah Zahra (Nindikayla Institute, 2023)
Liquidity is an important aspect that can be considered a bank's lifeblood. To maintain business continuity, banks must always manage liquidity effectively. Liquidity easing is one strategy to assist economic growth during the COVID-19 epidemic. Where macroprudential policies are used to ease liquidity restrictions. The government seeks to induce more outstanding lending to debtors to promote economic growth. On the other hand, this easing of liquidity is thought to help maintain bank operations solvent. This liquidity easing during the pandemic was carried out by reducing the reserve requirement and increasing the MPLB ratio. In addition, Bank Indonesia strengthened RIM by adding an export money order in its calculation. The goal of this research is to look at how macroprudential policy, such as the Statutory Reserves instrument, the Macroprudential Intermediation Ratio, and the Macroprudential Liquidity Buffer, affects the liquidity of traditional commercial banks in Indonesia from 2018 to 2021. The monthly data comes from the Financial Services Authority website, specifically the Indonesian Banking Statistics section. The researchers employed a multiple linear regression approach utilizing EViews 10 software to evaluate the three hypotheses. First, the Statutory Reserves have a negative and minor influence on commercial bank liquidity, according to the findings. Second, RIM has a good and considerable impact on commercial bank liquidity. Third, PLM has a considerable negative impact on commercial bank liquidity. Simultaneously, the three independent factors are discovered to impact commercial bank liquidity